2020
DOI: 10.1002/brb3.1947
|View full text |Cite
|
Sign up to set email alerts
|

Mild hypothermia improves brain injury in rats with intracerebral hemorrhage by inhibiting IRAK2/NF‐κB signaling pathway

Abstract: Objective To explore the effect of mild hypothermia on nerve injury by establishing a rat model of intracerebral hemorrhage (ICH), and to clarify the specific molecular mechanism of mild hypothermia in improving brain injury in ICH rats. Methods The rat model of ICH was established by collagenase injection. The neurological deficit score (NDS), brain tissue water detection, and Nissl staining were applied to detect the degree of brain injury. ELISA was used to analyze the expression of proinflammatory cytokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…IRAK2 is essential in the toll-like receptor and IL-1R signaling pathways, ultimately activating the NF-κB pathway [ 23 ]. The IRAK2/NF-κB signaling pathway plays roles in various diseases, such as brain injury [ 24 ]. We further explored the relationship between IRAK2 and the NF-κB signaling pathway in DN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IRAK2 is essential in the toll-like receptor and IL-1R signaling pathways, ultimately activating the NF-κB pathway [ 23 ]. The IRAK2/NF-κB signaling pathway plays roles in various diseases, such as brain injury [ 24 ]. We further explored the relationship between IRAK2 and the NF-κB signaling pathway in DN.…”
Section: Discussionmentioning
confidence: 99%
“…IRAK2 regulates various signaling pathways, including the nuclear factor-kappa B (NF-κB) signaling pathway [ 11 ]. IRAK2 can lead to TRAF6 ubiquitination, which is a key event in NF-κB activation [ 12 ]. The NF-κB signaling pathway is a critical cellular signaling pathway that regulates a wide range of biological processes, such as immune responses, inflammation, cell proliferation, and survival [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research by Metz suggested that a temperature of 32.5 -35 o C is conducive to reducing intracranial pressure [16]. In recent years, mild therapeutic hypothermia (with a temperature of 30 -35 °C) has achieved favorable outcomes in treating cerebral ischemia, cerebral hypoxia, and cerebral hemorrhage [17,18]. The results of the current study indicated that Angong Niuhuang Pil/mild therapeutic hypothermia significantly reduced the levels of NSE, S100B, and MBP proteins and mitigated the severity of neuron damage in the bleeding site.…”
Section: Discussionmentioning
confidence: 99%
“…At present, mild hypothermia has been used in lots of neurologic emergencies with considerable success, such as ischemic stroke, subarachnoid hemorrhage, traumatic brain injury, hepatic encephalopathy, cardiopulmonary arrest and so on [6]. It is reported that this may play its therapeutic role in a number of ways, such as regulated lysosomal function, autophagic ux, caspase-3 activation and the Wnt/b-catenin signaling pathway in our previous study [7][8][9], there are also calcium in ux, miR-122, IGF-1R/AKT pathway, IRAK2/NF-κB signaling pathway, etc [10][11][12]. In addition, DNA damage is de ned as physical or chemical changes in DNA within cells that affect the interpretation and transmission of genetic information [13].…”
Section: Introductionmentioning
confidence: 99%